Manajemen Sumber Daya Manusia (SDM) Berbasis Tekhnologi Untuk Pengembangan Kompetensi di Madrasah - Dluha Muthiatul Amroini; Ida Rindaningsih (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Human Resource Management (HRM) plays an important role in madrasa development, especially in the current digital era. With strategies that include planning, training, evaluation and follow-up, technology-based HRM can increase the efficiency and competence of teaching and staff. The use of technology, such as online training and data-driven performance management systems, facilitates better collaboration and more effective decision making. However, there are still challenges that must be faced, such as limited infrastructure, lack of training programs, limited budgets, and resistance to change. To overcome these issues, madrasas need to invest in technology, organize regular training, provide digital learning resources, and build a work culture that encourages innovation. By implementing these steps, madrasas can make maximum use of technology, improve the quality of education, and more effectively meet the needs of employees and students.